The importance of Instagram as a digital communication medium in tourism and hotel industry - Gašević Dragana; Jovičić Dragoljub; Pavlović Nataša (Marketing (Beograd. 1991), 2023)
The digital revolution has led to significant transformations when it comes to the ways companies communicate with their target markets. In addition to traditional media, digital channels and social networks are increasingly used as communication channels for establishing communication with real and potential customers. These changes are also identified when it comes to the business of service companies. The paper presents the basic characteristics of the Instagram social network with a focus on the application of Instagram in the business of four hotels from the Republic of Serbia. A detailed analysis of the available content on the hotel's official profiles refers to the period from October 1, 2022 to September 30, 2023. The results of the comparative analysis of secondary data showed that there are differences when it comes to the quantity of posts on a monthly basis. When it comes to the nature of the content that is published within the posts, general common elements characteristic of the area that is the subject of the analysis were observed. In addition, certain specificities have been identified by which hotels differ from each other, and which can be a source of differentiation and competitive advantage. Also, through the analysis, the posts shown in the paper that were most liked by the followers in the above-mentioned time period were identified. In addition to theoretical and practical contributions, the paper presents limitations and guidelines for future research.